DEIXIS TYPES IN MARRYING (MADURESE CULINARY WRITING) - Afiifah Al Rosyiidah; Darul Hikmah (Universitas 17 Agustus 1945 Surabaya, 2022)
. Every speaker should comprehend deixis to enhance the quality of communication with the interlocutor. This study investigates kinds of deixis and their references found in Madurese Culinary Writings. The data source of the study is the students’ Madurese Culinary Writings. It utilizes a qualitative research design. The data are gathered through observation and document review. During the data collection process, field notes are also used. The data are analyzed using an interactive model of data analysis, which includes data reduction, data display, and data verification/claim. The study's findings demonstrate that all types of deixes are found in Madurese Culinary Writings. Person deixis becomes the most frequent type of deixis including all data found, it has 70 data. The next position provides that place deixis is in the second position having 31 data. Then, discourse deixis has 21 data and time deixis has 13 data, and the lowest frequent type of deixis is social deixis having 6 data. Besides, the references found in this research: person deixes found are “I”, “we”, “us”, “my” as first person deixes; “You” as second person deixis; “They”, “it” as third person deixes which belong to person deixes; Place deixes found are “Serpang”, “Bangkalan”, “Arosbaya”; Time deixes found are “then”, “after”, “for 3-4 hours” ; discourse deixes found were “this”, “that”; and the last, social deixes found are “the seller”, ”my parents”.